Biodegradation and phenol tolerance by recycled cells of candida tropicalis NCIM 3556 - Varma, R. J.; Gaikwad, B. G. (International Biodeterioration & Biodegradation, 2009)
Resting cells of Candida tropicalis NCIM 3556 rapidly degraded almost completely 2 g L(-1) phenol in 16h. In this study, we explored the possibility of further increasing the efficiency of the culture by repeatedly reusing the cell for biodegradation. The effect of continuous recycling of whole cells of C. tropicalis, for biodegradation of phenol indicated that though with each recycle of the cell there was steady decline in phenol biodegradation the conversion was appreciable for five recycle (similar to 70%) and reached half-life of 50% after eleven recycles. Inhibition due to substrate, recycling of cells and adaptation of residual cell were estimated and an equation derived; which indicated that the cell resilience to phenol increased with each cycle and at the end of eleven recycle adaptation was 68%. However, when the adapted cells were sub cultured and showed marginal increase <10% in biodegradation. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Biodegradation; Candida tropicalis; Inhibition; phenol; Recycle; Tolerance